Architectural Design of an Electronic Based Government System (Case Study of XYZ district government) - Yanti, Lidya; Wirdiani, Ni Kadek Ayu; Githa, Dwi Putra (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2024)
The design of the Electronic-Based Government System Architecture to develop basic framework related to integration between SPBE Architecture domains, such as Business Processes, Services, Applications, Data and Information, Infrastructure, and Security. The results showed the SPBE mapping produces 17 business processes, 44 services, 112 applications, 123 data and information . SPBE infrastructure mapping has several divisions, such as computing facilities, platforms, and system integration. SPBE security mapping has several parts, such as technical standards and security procedures, SPBE security implementation, and SPBE security feasibility. The SWOT analysis concludes the strengths are business processes, services, and SPBE applications are sufficient to support the performance of government administration services and public services. The incomplete data used to complete the infrastructure and security domains of SPBE is a weakness, opportunity, and threat. The opportunity is can provide a clear direction in the implementation of SPBE has the opportunity to increase the SPBE index value. Keywords : Architectural Design, Government System Based Electronic, SPBE, SWOT Analysis.